DAMPAK BEBAN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP TURNOVER INTENTION PADA KARYAWAN PABRIK RJ BATU BATA DI BANYUASIN - Iswanto; Veronica, Meilin; DP, Mohammad Kurniawan (Universitas Bina Taruna Gorontalo, 2025)
This study aims to analyze the impact of workload and physical work environment on turnover intention among employees at the RJ Batu Bata Factory in Banyuasin. The sample used in this study consisted of 66 respondents selected through purposive sampling. The research method employed was multiple linear regression analysis. The results indicate that both workload and physical work environment have a positive and significant impact on employees' turnover intention. The results of the simultaneous test show that these two variables significantly influence employees' tendency to leave the company. The coefficient of determination shows that the majority of the variation in turnover intention can be explained by workload and physical work environment, while the remaining variation is influenced by other factors not identified in this study. Based on these findings, it is recommended that the management of the RJ Batu Bata Factory pay attention to workload and physical work conditions in order to reduce turnover intention among employees.